2008
DOI: 10.1158/1940-6207.capr-07-0017
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Smoking Cessation on Global Gene Expression in the Bronchial Epithelium of Chronic Smokers

Abstract: Cigarette smoke is the major cause of lung cancer and can interact in complex ways with drugs for lung cancer prevention or therapy. Molecular genetic research promises to elucidate the biological mechanisms underlying divergent drug effects in smokers versus nonsmokers and to help in developing new approaches for controlling lung cancer. The present study compared global gene expression profiles (determined via Affymetrix microarray measurements in bronchial epithelial cells) between chronic smokers, former s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 35 publications
1
68
2
Order By: Relevance
“…These genes were also found to be coordinately differentially expressed in the bronchial epithelium in an independent set of current and former smokers, suggesting that irreversible smoking-associated changes in gene expression could be used as a biomarker of prior exposure to tobacco smoke (4). The finding of irreversibly altered changes in bronchial airway gene expression among former smokers has been confirmed by two other groups using both microarray and SAGE (Serial Analysis of Gene Expression) platforms (5,6).…”
Section: Transcriptomic Studies Of Smoking-related Gene Expression Chmentioning
confidence: 68%
“…These genes were also found to be coordinately differentially expressed in the bronchial epithelium in an independent set of current and former smokers, suggesting that irreversible smoking-associated changes in gene expression could be used as a biomarker of prior exposure to tobacco smoke (4). The finding of irreversibly altered changes in bronchial airway gene expression among former smokers has been confirmed by two other groups using both microarray and SAGE (Serial Analysis of Gene Expression) platforms (5,6).…”
Section: Transcriptomic Studies Of Smoking-related Gene Expression Chmentioning
confidence: 68%
“…2007; Zhang et al. 2008). A long‐lasting effect after smoking cessation in asthmatics on corticosteroid responsiveness has also been suggested by the observation of an attenuated response to corticosteroid treatment in former smokers with asthma (Chaudhuri et al.…”
Section: Discussionmentioning
confidence: 99%
“…Another related study also reported in this issue of the journal was conducted by Zhang et al (7), who compared gene expression in cells obtained from bronchial brushes from never, current, and former smokers. Smoking effects on global gene expression were common across these studies.…”
mentioning
confidence: 90%